Zn(OAc)2·2H2O-Catalyzed One-Pot Efficient Synthesis of a-Amino Nitriles - Venkata Rami Reddy, V.; Saritha, B.; Ramu, R.; Varala, Ravi; Jayashree, A. (Asian Journal of Chemistry, 2014)
A mild, efficient one-pot three component strecker reaction involving electronically and structurally divergent aldehydes, amines and trimethly silyl cyanide in chloroform as solvent at room temperature was accomplished in moderate to excellent yields using an inexpensive and readily available catalyst, Zn(OAc)2.2H2O.